Evolution of binding affinity in a WW domain probed by phage display. - Dalby, P. A. (Cold Spring Harbor Laboratory Press, 2000)
The WW domain is an approximately 38 residue peptide-binding motif that binds a variety of sequences, including the consensus sequence xPPxY. We have displayed hYAP65 WW on the surface of M13 phage and randomized one-third of its three-stranded antiparallel beta-sheet. Improved binding to the hydrophobic peptide, GTPPPPYTVG (WW1), was selected in the presence of three different concentrations of proteinase K to simultaneously drive selection for improved stability as well as high-affinity binding. While some of the selected binders show cooperative unfolding transitions, others show noncooperative thermal unfolding curves. Two novel WW consensus sequences have been identified, which bind to the xPPxY motif with higher affinity than the wild-type hYAP65 WW domain. These WW domain sequences are not precedented in any natural WW domain sequence. Thus, there appear to be a large number of motifs capable of recognizing the target peptide sequence, only a subset of which appear to be used in natural proteins.